Cardiovascular disease risk in offspring of polycystic ovary syndrome - Shawky, Noha M. (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome (PCOS) is the most common endocrine disorder affecting women at reproductive age. PCOS diagnosis (Rotterdam criteria) is based on the presence of two out of three criteria; clinical and/or biochemical hyperandrogenism, oligo- or an-ovulation and polycystic ovaries. PCOS women suffer from a constellation of reproductive and metabolic abnormalities including obesity and insulin resistance. PCOS women also have increased blood pressure and increased risk of cardiovascular diseases (CVD). In-utero, offspring of PCOS women are exposed to altered maternal hormonal environment and maternal obesity (for most of PCOS women). Offspring of PCOS women could also be subject to genetic susceptibility, the transgenerational transmission of some of the PCOS traits or epigenetic changes. Offspring of PCOS women are commonly reported to have an abnormal birth weight, which is also a risk factor for developing CVD and hypertension later in life. Although studies have focused on the growth pattern, reproductive and metabolic health of children of PCOS women, very limited number of studies have addressed the risk of hypertension and CVD in those offspring particularly as they age. The current narrative review is designed to summarize the available literature (both human studies and experimental animal studies) and highlight the gaps in addressing hypertension and CVD risks in offspring of PCOS women or hyperandrogenemic female animal models.